Synthesis and Characterization of 4-amino-N'-[(1E)-1-(2-hydroxy-6-methyl-4-oxo-4H-pyran-3-yl)ethylidene]benzohydrazide and its Cu(II), Ni(II), Zn(II) and Mn(II) Complexes - Anarado, Chigozie John Onyinye; Iziga, Chinasa Grace; Ibeji, Collins Ugochukwu; Babahan-Bircan, Ilknur; Coban, Burak; Cömert, Füsun; Anarado, Charity Ebere (Universitas Jenderal Soedirman, 2023)
New benzohydrazone compound, 4-amino-N'-[(1E)-1-(2-hydroxy-6-methyl-4-oxo-4H-pyran-3-yl)ethylidene] benzohydrazide (HL1) and its Cu(II), Ni(II), Zn(II) and Mn(II) complexes were synthesized. The structures of HL1 and its complexes were elucidated by elemental analysis and IR, UV-Vis, 1H and 13C NMR spectroscopy and mass spectrometry. The infrared spectral data of the complexes revealed that HL1 coordinated with the metal ions through azomethine nitrogen, enolic oxygen and amide carbonyl oxygen atoms, hence, HL1 behaves as a monobasic tridentate ligand. UV-Vis data revealed that Zn(II) and Mn(II) complexes adopted octahedral geometry, while Cu(II) and Ni(II) complexes had five-coordinate and square-planar geometries respectively. The mass spectra data and elemental analysis values are in accordance with the calculated values for the suggested molecular formula of the complexes, a confirmation of the 1:1 ligand to metal stoichiometry in case of Cu(II) complex and 2:1 ligands to metal stoichiometry in case of the other complexes.